Endovascular Stent Graft Repair is an Effective and Safe Alternative Therapy for Arteriovenous Graft Pseudoaneurysms. Issue 5 (November 2016) - Wong, W.K.; Su, T.-W.; Cheng, W.-L.; Yang, H.-T.; Wei, W.-C.; Ko, P.-J.
Abstract : Objective/Background: Pseudoaneurysm formation occurs in 2–10% of hemodialysis arteriovenous grafts (AVGs). Surgical repair often requires pseudoaneurysm resection, interposition graft placement, and insertion of a catheter as a bridge. Endovascular stent graft repair is a controversial alternative therapy. This study was performed to examine the effectiveness and mid-term outcomes of stent graft repair for AVG pseudoaneurysms. Methods: All patients who had undergone stent graft repair for AVG pseudoaneurysms between December 2012 and July 2015 were identified from hospital medical records for retrospective analysis. Outcome measures were technical success, early and late complications, and primary and secondary patency rates. Results: A total of 37 stent graft repairs of AVG pseudoaneurysms were performed in 35 patients (42.9% men; mean age 66.9 years). The mean time from AVG creation to pseudoaneurysm repair was 69 months. The indications of treatment (as per the institutional policy) were large pseudoaneurysm (56.7%), impending rupture (27.1%), and bleeding (16.2%). Mean pseudoaneurysm diameter was 23.0 mm. The most common diameter and length of stent graft used were 7 mm (67.6%) and 50 mm (48.6%), respectively. Technical success was 100%. Only one early complication occurred after stent graft repair, which was due to recurrence of the pseudoaneurysm as a result of a short landing zone. Late complications included infection (17.1%) and thrombosis (37.1%). The 1, 6, and 12 month primary patency rates were 89.2%, 55.5%, and 22.0%, respectively. The 1, 6, and 12 month secondary patency rates were 100%, 88.6%, and 78.6%, respectively. The median follow up was 12.3 months. Conclusions: The study demonstrates that endovascular stent graft repair is an effective and safe alternative therapy for AVG pseudoaneurysms. However, the rate of thrombosis and infection was high and needs to be balanced against open surgery in future studies.